The Valuation of New Ventures - Luigi Sereno (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
Traditional tools fail to capture the value of new ventures, such as R&D projects and start-up companies, because of their dependence on future events that are uncertain at the time of the initial decision. In the real options setting the value of these investments is the value of the follow-on opportunities they may create. Our aim is to study the multicompound option approach to value sequential investment opportunities taking into account multiple interactions among real options.
Keywords: 330; Investition; Theorie; Realoptionsansatz